2018
DOI: 10.1007/s00709-018-1211-7
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer labdane diterpenoids from adventitious roots of Andrographis paniculata: augmentation of production prospect endowed with pathway gene expression

Abstract: Andrographolide (AD) is the time-honoured pharmacologically active constituent of the traditionally renowned medicinal plant-Andrographis paniculata. Advancements in the target-oriented drug discovery process have further unravelled the immense therapeutic credibility of another unique molecule-neoandrographolide (NAD). The escalated market demand of these anti-cancer diterpenes is increasingly facing unrelenting hurdles of demand and supply disparity, attributable to their limited yield. Callus and adventitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…6-benzyloaminopurine reduce the amount of compounds witch are biosynthesized on the MEP pathway 48 , similar as in our case. The other studies indicate the influence of NAA on the MEP pathway 49 , 50 . Our results indicate that this plant growth regulator stimulated the biosynthesis of identificed secondary metabolites.…”
Section: Discussionmentioning
confidence: 95%
“…6-benzyloaminopurine reduce the amount of compounds witch are biosynthesized on the MEP pathway 48 , similar as in our case. The other studies indicate the influence of NAA on the MEP pathway 49 , 50 . Our results indicate that this plant growth regulator stimulated the biosynthesis of identificed secondary metabolites.…”
Section: Discussionmentioning
confidence: 95%
“…Accumulating evidence has shown that dietary botanical compounds, such as herbal medicines, have increasingly important roles in the field of cancer treatment, both as therapeutic agents and adjunctive treatments to traditional therapies (10,47). Andrographolide is a C20 labdane diterpenoid derived from the traditional Chinese medicine Andrographis paniculate (12)(13)(14), which has been found to have cytotoxic/anti-tumorigenic potential in various malignancies (14,20,22,(24)(25)(26)28). Intriguingly, Andrographolide was demonstrated to alter multiple cancer-associated signaling pathways, such as BAX-dependent apoptotic signaling in breast cancer (22), PI3K/AKT/mTOR-dependent signaling in leukemia (20) and glioblastoma (24), p38 signaling in melanoma ( 14), STAT3/AKT activation in pancreatic cancer (28), and the Src/MAPKs/AP-1 axis (25) and TLR4/NF-kB/MMP-9 pathway (32) in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, most of these dietary botanicals function by targeting multiple cancer-associated pathways to exert anti-tumorigenic effects on cancer progression (11). Andrographolide is a C20 diterpenoid lactone, which is an active ingredient derived from the traditional Chinese herbal medicine Andrographis paniculate (12)(13)(14). Because of its ability to circulate in the bloodstream (15)(16)(17), Andrographis…”
Section: Introductionmentioning
confidence: 99%
“…Evidently, the higher expressions of ApDXS and ApHMGR genes at 25 µM and 50 µM with higher andrographolide synthesis indicated the crucial role of these two genes and the synergy between MVA/MEP pathways. Singh et al [48] reported that untreated control, in vitro adventitious root cultures of A. paniculata have shown high-expression levels of MVA pathway genes (HMGR1/2) and low expression of MEP pathway genes (DXS1/2 and HDR1/2). However, in our study, an external stimulus JA not only enhanced the MEP pathway-related gene expression, but also significantly influenced MVA pathway genetic.…”
Section: Discussionmentioning
confidence: 99%